Dielectric Permittivity of Human Ejaculate at Normo- and Pathospermia after Interaction with Cryoprotective Medium - Rodionova, V. L.; Tchoob, N. N.; Schegoleva, T. Yu.; Todorov, P. (Problems of Cryobiology and Cryomedicine, 2004)
Using the SWF-dielectrometry the real ε′ and imaginary ε″parts of dielectric permittivity were shown to be changed depending on spermatogenesis pathology. A glycerol-lactose-yolk cryoprotective medium affects the state of the ejaculate water component, decreases the free water content in spermatozoa.